ISOLATION AND IDENTIFICATION OF UTERINE BACTERIA ASSOCIATED WITH ENDOMETRITIS IN COWS - RAUTELA, R; DAS, GK; PRASAD, S; KUMAR, A; ABHISHEK; NARAYANAN, K; PRASAD, JK (The Indian Journal of Animal Reproduction, 2022)
Twelve cows with the clinical history of repeat breeding were sampled for uterine swab followed by the identification and isolation of bacteria using various conventional and biochemical tests. Out of 12 samples collected, five types of isolates were identified. Among the isolates, Corynebacterium spp. (32%) was the most predominant bacteria followed by Bacillus spp. (28%), Staphylococcus spp. (24%), E. coli (12%) and Salmonella spp. (4%).